The economic value of grassland ecosystem services: A global meta‐analysis. Issue 1 (30th April 2022) - Liu, Huifang; Hou, Lingling; Kang, Nannan; Nan, Zhibiao; Huang, Jikun
Abstract: Background: Grasslands provide a wide variety of ecosystem services that contribute to human wellbeing. While an increasing number of studies are evaluating the monetary value of grassland ecosystem services, most of them focus on specific grassland ecosystem services at regional or local scales, and they use different assessment methods. Methods: This paper provides a comprehensive assessment of the economic value of global grassland ecosystem services based on a meta‐analysis of 702 observations from 134 primary studies. Results: The economic values of different ecosystem services cover a wide range of grassland types, regions, and estimation methods. The annual economic value per hectare ranges from $3955 for semidesert grasslands to $5466 for tropical grasslands. On average, regulating services have the highest value, which is approximately four times that of provisioning services or approximately eight times that of food supply services. Several factors impact the estimated ecosystem service values, including the evaluation method, source and year of publication, and study site. The results indicate that the annual economic value of global grasslands exceeds $20.8 trillion. Conclusions: The findings of this study not only provide useful information for understanding the economic value of various ecosystem services associated with different types of grasslands but also have important policy implications for the ecological conservation of grassland globally. Abstract : Economic value differs by types of grassland and ecosystem services.